Counseling Improves Anemia Prevention Behavior of Pregnant Women - Mira Triharini; Tiyas Kusumaningrum; Christine Octaviani (Universitas Airlangga, 2009)
Introduction: Pregnancy closely associated with anemia, where the condition of mothers with Hb under 11gr% in 1st and 3rd trimester or Haemoglobin (Hb) levels below 10.5 g% in 2nd trimester. Knowledge, attitudes and practices of pregnant women on preventing anemia during pregnancy is one of the factors that influence incidence of anemia which affects the health of babies. Objective of this study was to explain the effect of counseling toward anemia prevention behaviour (knowledge, attitude, practice) of pregnant women. Method: A pre-experimental (one group pretest-posttest) simple random sampling design was used in this study. Population of this study was all pregnant women in Mrs. Wolita midwife practice Surabaya ( as many as 30 pregnant women a month). Sample of these 28 pregnant women were recruited over period of this study. Independent variable was counseling, while the dependent variable were knowledge, attitudes and practice. Data were collected by using questionnaires and analyzed with the Wilcoxon Signed Rank Test with significance level of α ≤0.05. Result: The result showed that counseling effected behaviour (knowledge, attitude and practice) of pregnant women on anemia prevention with significance level p=0.000 (knowledge); p=0.007 (attitude) and p=0.027 (practice). It can be concluded that counseling or health education about prevention of pregnancy anemia is needed for pregnant women. Discussion: It is recomended that regular counseling must be provided by counselor to prevent anemia during pregnancy. Haemoglobin of pregnant women should also be checked regularly in the midwife practices, as a first step effort to decrease the incidence of anemia in pregnant women.